(untitled) (Journal of Information Technologies in Education (ITE), 2017)
The creation of strong basic schools with the network of branches and other networked educational organizations in the Ukrainian education system requires from leading cadres the possession of the basics of network management. The article deals with the questions of the process of forming professional competencies of heads of networked educational entities in conditions of postgraduate pedagogical education. The features of learning model which based on the active use of information and communication technologies are revealed have been disclosed; components of the open educational environment (cognitive, social and educational) and their influence on the process of training leading cadres; advantages of using Internet technologies for educational purposes. The article describes the experience of organizing a continuous educational process by using the funds of information and communication technologies: websites, distance learning courses,social communities, and other Internet services. At the same time, heads of educational institutions are united in cluster formations by type of educational institutions, the level of providing educational services, the direction of professional interests, preferences, and also for the joint development of managerial algorithms in certain typical situations and for solving typical professional problems. In such a model of learning, knowledge is produced by participants independently during active activity by joint search, processing, and analysis of information,solving problem situations, discussions, debates, etc.